Oncocytic carcinoma of the parotid gland with facial nerve invasion. (29th July 2011) - Leahy, Travis; Sader, Chady
Abstract : Approximately 3% of all head and neck neoplasms originate in the parotid gland and less than 1% are oncocytic. We present the rare case of a 44-year-old man with oncocytic carcinoma of the parotid gland with facial nerve invasion and discuss the characteristics of this rare entity.